Legal Aıd For Cıvıl Servants In Corruptıon Cases Related To Equıtable Procurement Of Goods/Servıces - Kemilau Mutik; Abdul Rachmad Budiono; Yohanes Sogar Simamora; Moh. Fadli; Shinta Hadiyantina (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
In the context of legal science, the value of justice for all Indonesian people as stated in Pancasila, the 5th Precept is termed as substantive justice, namely justice that is actually felt by the community and created through legal formation. In these precepts, the essence of justice is based on and imbued with justice in the life of the nation, justice towards the creator and fellow human beings. Laws in Indonesia must be in line with Pancasila. Equitable law enforcement means that every community must get equal treatment before the law (equality before the law) and fair or access to justice, especially civil servants in carrying out their duties and obligations as government officials. Legal aid has an important position in every criminal justice system and helps to achieve a "fair legal process". Law Number 20 of 2023 concerning State Civil Apparatus article 21 paragraph (2) letter (g) states that "State Civil Apparatus are entitled to obtain "legal aid". The provision of legal aid as part of access to justice for the community is elaborated in article 28D paragraph (1) of the 1945 Constitution which states that "everyone has the right to recognition, guarantees, protection and certainty of a just law and equal treatment before the law", this is also regulated in Law Number 16 of 2011 concerning Legal Aid in article 3 which states that "the organizer of the legal aid program shall be responsible for the provision of legal aid to the public".